Development and validation of a patient-specific model to predict postoperative SIRS in older patients: A two-center study - Li, Xiaoyue; Lu, Yaxin; Chen, Chaojin; Luo, Tongsen; Chen, Jingjing; Zhang, Qi; Zhou, Shaoli; Hei, Ziqing; Liu, Zifeng (Frontiers in Public Health, 2023)
Abstract Introduction Postoperative systemic inflammatory response syndrome (SIRS) is common in surgical patients especially in older patients, and the geriatric population with SIRS is more susceptible to sepsis, MODS, and even death. We aimed to develop and validate a model for predicting postoperative SIRS in older patients. Methods Patients aged ≥65 years who underwent general anesthesia in two centers of Third Affiliated Hospital of Sun Yat-sen University from January 2015 to September 2020 were included. The cohort was divided into training and validation cohorts. A simple nomogram was developed to predict the postoperative SIRS in the training cohort using two logistic regression models and the brute force algorithm. The discriminative performance of this model was determined by area under the receiver operating characteristics curve (AUC). The external validity of the nomogram was assessed in the validation cohort. Results A total of 5904 patients spanning from January 2015 to December 2019 were enrolled in the training cohort and 1105 patients from January 2020 to September 2020 comprised the temporal validation cohort, in which incidence rates of postoperative SIRS were 24.6% and 20.2%, respectively. Six feature variables were identified as valuable predictors to construct the nomogram, with high AUCs (0.800 [0.787, 0.813] and 0.822 [0.790, 0.854]) and relatively balanced sensitivity (0.718 and 0.739) as well as specificity (0.718 and 0.729) in both training and validation cohorts. An online risk calculator was established for clinical application. Conclusion We developed a patient-specific model that may assist in predicting postoperative SIRS among the aged patients.